Ru/La2O3–SiO2 catalysts for hydrogen production in membrane reactors - Faroldi, Betina María Cecilia (2011)
Binary La2O3–SiO2 supports were employed to obtain active, stable Ru catalysts with high dispersions for the dry reforming of methane. Supports with 15, 27, 40 and 50 wt.% of La2O3 were prepared by incipient wetness impregnation of La(NO3)3 on SiO2. The Ru loading was 0.6 wt.% for all catalysts. The solids were evaluated in a fixed-bed reactor under differential conditions. Previously, they were reduced at 550 ◦C. All the formulations were stable for at least 100 h on stream. Subsequently, the most active catalyst (Ru/La2O3(50)–SiO2) was tested in a membrane reactor using different feed mixtures with and without O2. The reactor configuration was formed by a fixed-bed reactor followed by a membrane reactor. The methane conversion increased when the CO2/CH4 ratio increased from 1.0 to 1.9 and when oxygen was added to the feed. Operating under conditions of combined reforming (oxygen addition) and CO2/CH4 ratio equal to 1, a high production of hydrogen was also achieved in the membrane reactor.